Gastronomy and Wines in the Alentejo Portuguese Region: Motivation and Satisfaction of Tourists from Évora - Amaral, Rui (2016)
Abstract: Food and winemaking are a recognized tangible and intangible cultural heritage of Portugal. From the relationship between these two components, a strategic product emerged with a considerable potential for tourism industry, which is not ignored by many of tourism organizations. This chapter intends to analyze food and winemaking from a tourism demand perspective. Particularly, this study describes visitors’ profile, including, their motivations, their knowledge about the enological and gastronomic resources and the degree of satisfaction. A total of 308 questionnaires were collected between February and May of 2012, from the visitors that visited the historic center of Évora (Alentejo-Portugal). Results reveal a visitor profile associated with regional cuisine and wine products from Portugal. Moreover, visitors’ evidenced a high level of knowledge regarding the Portuguese cuisine and regional wines; although this not matches with their primary motivation for visit the city of Évora. R. Amaral